PENGARUH STRATEGI PELAYANAN OUTLET DAN HUBUNGAN DENGAN OUTLET TERHADAP KINERJA SELLING-IN SERTA DAMPAKNYA TERHADAP KINERJA PEMASARAN (Studi : Outlet yang menjual Memory Card Sandisk di Semarang) - Kustriantomo, Fajar; Santosa, Suryono Budi (Diponegoro Journal of Management, 2015)
A good marketing performance showed a high level of sales, increasing the number of  sales  both  in  units  of  the  product  or  in  monetary  units.  The improved marketing performance  marked also with good sales growth from year to year and higher growth than similar competitors and has a broad customer compared to previous years. This study aimed to analyze the influence  of strategy and service outlets and outlet connection with the performance of selling-in and impact on the performance of marketingThis study uses multiple linear  regression  analysis using SPSS. The population used is the customer's customer Buana Gemilang Creatindo Semarang in January-August 2014. The samples used were 100 people with sample selection techniques using non- probability sampling accidental samplingThe results  show that  the strategy of influence  on the performance  and service outlets selling-in, relationships affect the performance of outlets selling-in, service strategy affect the performance of marketing outlets, outlets Relations affect the performance of selling-in, Performance selling-in effect on the performance of marketing, strategy service outlets and  outlet connection directly influence the performance of  marketing through selling-in performance.